(untitled) (Baghdad Science Journal, 2025)
Isocratic high performance liquid chromatography on reversed phase a (150x 4.6 mm I.D), 5 ?m ?-Bondapak RP-8 column (with acidic mobile phase allow the separation of doxcycycline hydrochloride with low detection limit of 0.2 µg/ml detected by UV set at 226 nm. The method was validated for Doxycycline between 0.156- to 5 µg/ml. The concentration of doxycycline was assessed in two single dose randomized crossover studies with intervals of one week between two period. In sera of 20 adults healthy male volunteers with average age of (42 + 10) year, body weight 48-85 kg, body height of (160-185cm) after a single dose of doxycycline hydrochoride 100 mg in form of capsules were orally administrated for both formulations. The blood samples (2ml) were drawn concomitantly from 0.5 – 24 hours. µg The pharmacokinetics parameter were obtained from the mean serum concentration measured at various sampling times for both formulations. The maximum peak concentration (Cmax) of doxycycline reference drug from Pfizer In serum was (3.1 +0.094 µg /ml) attained in 2 hrs. While the maximum concentration (Cmax) of test drug doxysam (2.8 +0.098 µg /ml) attained in about 2 hrs, both drug have long elimination time with half time of approximately (13 hrs.) Both test and reference drug were show no significant difference in pharmacokinetics parameters, so they were considered to be bioequivalent.